Reduction of FFA in Kapok Randu (Ceiba pentandra) Seed Oil via Esterification Reaction Using Sulfuric Acid Catalyst: Experimental and Kinetics Study - Kusumaningtyas, Ratna Dewi; Akbar, Muhammad Hafizt; Widjanarko, Dwi (Jurnal Bahan Alam Terbarukan, 2019)
The rapid growth of the population and economy has boosted up the necessity of fuel and energy source. Until now, the world’s dependency on fossil fuel as the primary energy supply is still high. On the other hand, it has been known that the fossil-based oil and gas reserves are shrunk. Hence, it is urgent to develop alternative energy sources, which are renewable and environmentally friendly, to anticipate the energy insufficiency. Biodiesel is among the prospective renewable energy due to its advantages. Biodiesel (fatty acid methyl esters) is a type of biofuel which is derived from vegetable oil or animal fat. There are various vegetable oils that can be used as raw material for biodiesel production. However, non-edible oils are usually preferred to be selected as a biodiesel feedstock to evade the conflict between food and energy needs. Kapok Randu (Ceiba pentandra) seed oil is a type of non-edible oil which is cheap and can be employed as biodiesel feedstock. However, this oil has high free fatty acid (FFA) content (8.89%). Thus, it cannot directly undergo transesterification reaction to produce biodiesel since the FFA will react with alkaline catalyst to produce soap. The FFA content in Kapok Randu seed oil needs to be decreased until it is lower than 2%. Hence, prior to transesterification reaction, esterification of Kapok Randu seed oil with methanol in the presence of acid catalyst should be conducted to decrease the FFA content. In this work, esterification reaction was performed in the presence of sulfuric acid catalyst. The reactions were conducted at the molar ratio of oil to methanol of 1:12 at the temperature of 40, 50, and 60 ℃ for 120 minutes. The optimum reaction conversion was 95.14%, achieved at the reaction temperature of 60 ℃. Kinetics study using homogeneous models was also performed. It was revealed that the reaction was appropriate with the irreversible second order reaction model. The reaction rate constant (k), activation energy (Ea), and frequency factor (A) were 4.95 L / mole.min, 30,799.21 J/ mole and 338.744 / min, respectively.